2015
DOI: 10.5753/cbie.sbie.2015.647
|View full text |Cite
|
Sign up to set email alerts
|

Musikinésia: Jogo Eletrônico para o Aprendizado de Teclado Musical

Abstract: This paper presents the educational game Musikinésia which was designed to help students of music courses in the identification of a musical keyboard, in addition to teaching other basic musical concepts such as tempo, accidentals and music reading. Beyond discussing how game-based learning can effectively contribute with teaching-learning process of musical content and specific care required for good educational games development, the main stages of the Musikinésia's development process are presented, emphasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
1
0
3
Order By: Relevance
“…Schell (2008) indicated that mechanics is the main element in games [34]. It can constrain players' behavior through the procedures and rules of the game [35]. De Mira Gobbo et al (2021) proposed that the game's mechanics includes the game's rules, levels, and structure [36].…”
Section: Mechanicsmentioning
confidence: 99%
“…Schell (2008) indicated that mechanics is the main element in games [34]. It can constrain players' behavior through the procedures and rules of the game [35]. De Mira Gobbo et al (2021) proposed that the game's mechanics includes the game's rules, levels, and structure [36].…”
Section: Mechanicsmentioning
confidence: 99%
“…O trabalho proposto por Bordini et al [2015] apresenta um jogo educacional denominado Musikinésia. O jogo possui o objetivo de auxiliar os alunos de cursos de música a identificar as teclas de um teclado musical.…”
Section: Trabalhos Relacionadosunclassified
“…A equipe responsável pelo projeto foi composta por quatro estudantes de graduação (cursos de Música, Ciência da Computação, Engenharia da Computação e Imagem e Som) e um aluno de mestrado em Educação, que atuaram como projetistas, desenvolvedores, ilustradores, músicos e especialistas no conteúdo, além de receber apoio da coordenação de docentes das áreas de Música, Computação e Educação. Todo o processo de design e desenvolvimento do jogo é mais bem detalhado em Bordini et. al.…”
Section: Desenvolvimentounclassified